Basement membrane properties and their recapitulation in organ-on-chip applications. (June 2022) - Salimbeigi, Golestan; Vrana, Nihal E.; Ghaemmaghami, Amir M.; Huri, Pinar Y.; McGuinness, Garrett B.
Abstract: Drug discovery and toxicology is a complex process that involves considerable basic research and preclinical evaluation. These depend highly on animal testing which often fails to predict human trial outcomes due to species differences. Coupled with ethical concerns around animal testing, this leads to a high demand for improved in vitro cell culture platforms. Current research efforts, in this regard, however, are facing a challenge to provide physiologically relevant in vitro human organ models for a reliable assessment of the physiological responses of the body to drug compounds and toxins. The latest development in in vitro cell culture models, organ-on-chips (OOCs), seek to introduce more realistic models of organ function. Current OOCs often use commercial porous polymeric membranes as a barrier membrane for cell culture which is challenging due to the poor replication of the physiological architectures. Better recapitulation of the native basement membrane (BM) characteristics is desirable for modelling physical (e.g. intestine, skin and lung) and metabolic (e.g. liver) barrier models. In this review, the relevance of the physical and mechanical properties of the membrane to cell and system behaviour is elucidated. Key parameters for replicating the BM are also described. This review provides information for future development of barrier organ models focusing on BM-mimicking substrates as a core structure. Graphical abstract: Image 1